Experimental Study on Prototype of Printed Circuit Heat Exchanger - Zhang, Dongxu; Zhao, Minfu; Liang, Peng; Li, Weiqing (Frontiers in Energy Research, 2022)
The printed circuit heat exchanger (PCHE) is the key equipment of the supercritical carbon dioxide Brayton cycle applied to sodium cooled fast reactor. It is required that the equipment not only can operate in high temperature and high pressure environment but also has high efficiency and compact structure. The China Institute of Atomic Energy has carried out the research on a sodium-supercritical carbon dioxide PCHE and has designed and manufactured a heat exchanger prototype with the heat transfer power of 50 kW. In addition, the supercritical carbon dioxide test loop and sodium test loop have been built to test the performance of the heat exchanger prototype. The conclusions are as follows: 1) The heat exchange power of the heat exchanger under rated working condition is 54.2 kW, and the deviation is around 8%, which meets the design requirements; 2) With the increase of the flow ratio of sodium to carbon dioxide, the temperature difference at the high temperature end decreases, and the temperature difference at the low temperature end increases; 3) The change of flow rate of the carbon dioxide has a great influence on heat transfer power; 4) The total heat transfer coefficient of the heat exchanger increases with the increase of the pressure of carbon dioxide; when the pressure increases from 15.5 to 20 MPa, the total heat transfer coefficient increases by 12.8%.